The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/ijc.32823
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking, chewing habits, alcohol drinking and the risk of head and neck cancer in Nepal

Abstract: Although tobacco smoking, pan chewing and alcohol drinking are important risk factors for head and neck cancer (HNC), the HNC risks conferred by products available in Nepal for these habits are unknown. We assessed the associations of tobacco smoking, chewing habits, and alcohol drinking with HNC risk in Nepal. A case-control study was conducted in Nepal with 549 incident HNC cases and 601 controls. Odds ratios (OR) and 95% confidence intervals (CI) were estimated using unconditional logistic regression adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 47 publications
4
20
1
1
Order By: Relevance
“…This region has high incidence rates for oral cancer because, in addition to tobacco smoking, tobacco chewing as well as chewing betel quid and areca nut also poses a major risk in acquiring oral cavity cancer. In a study, tobacco consumption and alcohol drinking were responsible for almost 85.3% of head and neck cancers with a population attributable fraction (PAF) of 24.3% for smoking, 39.9% for tobacco chewing, and 23.0% for alcohol drinking [ 37 ]. The interplay of the trends of the two risk factors to which the highest proportion of cancer DALYs in Nepal could be attributed to tobacco and alcohol use; and their consumption in Nepal has increased during this period [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…This region has high incidence rates for oral cancer because, in addition to tobacco smoking, tobacco chewing as well as chewing betel quid and areca nut also poses a major risk in acquiring oral cavity cancer. In a study, tobacco consumption and alcohol drinking were responsible for almost 85.3% of head and neck cancers with a population attributable fraction (PAF) of 24.3% for smoking, 39.9% for tobacco chewing, and 23.0% for alcohol drinking [ 37 ]. The interplay of the trends of the two risk factors to which the highest proportion of cancer DALYs in Nepal could be attributed to tobacco and alcohol use; and their consumption in Nepal has increased during this period [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary national intervention strategies to limit tobacco use in Nepal are prescribed in the Tobacco Product (Control and Regulatory) Act, which was signed into law in 2011. This law requires the size of warning labels on tobacco products to cover at least 90% of the package area, prohibits the distribution and advertisement of tobacco products to children, levies a tax on tobacco products, and bans smoking in public areas, among other provisions [ 42 , 43 ]. Worksite smoking cessation interventions have shown some success in developed countries [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows that the risk of oral and pharyngeal cancer and oral leukoplakia in general increases with an increasing dose–response measured by the number of cigarettes per day and the number of years of exposure and declines with the duration of smoking cessation. [ 26 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that when combined these risk factors with alcohol consumption, the risk increases considerable for head and neck cancer. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%